1998
DOI: 10.1159/000053091
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Growth Hormone Administration Frequencies on Growth in Growth Hormone-Deficient Patients

Abstract: In two different groups of clinically prepubertal children (bone age ≤8 years) with isolated growth hormone deficit we have evaluated either if the substitutive therapy administered by pump (permitting between 20.00 and 08.00 h the association of continuous and intermittent subcutaneous growth hormone administration) could improve growth (study A) or if a 3 times/week schedule treatment could be performed without any negative effect on growth with respect to 6 injections/week (study B). All patients had been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…The results of the study confirm our previous findings that baseline serum IGF-I and IGFBP-3 levels in infants with NOFTT are not different from the age-matched controls [31]. We therefore suggest that serum IGF-I and IGFBP-3 concentrations cannot be used as an index of nutritional status or a marker for faborable response to nutritional supplementation in infants.…”
Section: Discussionsupporting
confidence: 87%
“…The results of the study confirm our previous findings that baseline serum IGF-I and IGFBP-3 levels in infants with NOFTT are not different from the age-matched controls [31]. We therefore suggest that serum IGF-I and IGFBP-3 concentrations cannot be used as an index of nutritional status or a marker for faborable response to nutritional supplementation in infants.…”
Section: Discussionsupporting
confidence: 87%
“…Our results are reassuring with regard to the treatment of children and adolescents in whom levels of adherence are often suboptimal; the dose increase prescribed by the physician might compensate (at least in part) for the poor adherence, provided that the mean daily dose of rhGH is high enough. In agreement with our findings, several studies have shown that for an rhGH dose of 0.03 mg/kg.d, three injections a week were as effective as six or seven a week ( 26 , 27 ). However, another study concluded that daily injections were superior ( 28 ).…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with the study of Smith et al, who demonstrated no difference in auxological parameters after 12 months of GHT in GHD children receiving GH three or six days a week or twice daily six days a week, assessing the main role played by the GH dose and not by the regimen of administration [14]. Similar results were shown a few years later by Cavallo et al, who observed no difference in auxological parameters during the 3 times/week treatment schedule started during the follow-up in already treated GHD children compared to the previous 6 times/week schedule [15]. The comparable auxological effect of the 2 regimens of GHT has also been demonstrated in patients with Turner syndrome randomized to 3 or 6 times weekly GHT [28].…”
Section: Discussionmentioning
confidence: 58%
“…The clinical outcomes of daily versus TIW GH administration were already studied many years ago. The TIW regimen seems to produce similar effects to those of daily injections in both adults and children with GHD [1315], although several studies have reported that the daily GH administration in children was more effective than TIW dosing on linear growth [16, 17]. However, to date, the metabolic effects of GHT given in an alternative regimen in GHD patients have only been evaluated in adults and never in children.…”
Section: Introductionmentioning
confidence: 99%